2019
DOI: 10.1155/2019/8435019
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hepatitis B Infection Burden, Comorbidity and Pregnancy Outcome in a Low-Income Population on the Myanmar-Thailand Border: A Retrospective Cohort Study

Abstract: Objectives. Hepatitis B virus (HBV) was believed to have minimal impact on pregnancy outcomes apart from the risk of perinatal transmission. In more recent years, there have been reports of adverse associations, most consistently preterm birth (PTB), but this is in the context of high rates of caesarean section. The aim of this study was to explore the association of HBV on pregnancy outcomes in marginalized, low-income populations on the Myanmar-Thailand border. Methods. HBsAg positive (+) point of care rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…A common application of these HBsAg POCs is to measure seroprevalence in general or specific subpopulations in low-resource settings [ 52 , 53 , 54 , 55 , 56 ]. They have also been used in mass screening programs for hepatitis B in both community outreach [ 24 , 57 ] and health-facility-based screening [ 52 , 53 , 58 , 59 , 60 , 61 , 62 ] in low-resource settings and shown great public health benefits. For example, in a community-based outreach screening program conducted in 75 camps in Southern India [ 63 ], the “screen and vaccinate/linkage to care” strategy led to over 7700 vaccinations in the camps and 162 people with high viral load getting treatment.…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…A common application of these HBsAg POCs is to measure seroprevalence in general or specific subpopulations in low-resource settings [ 52 , 53 , 54 , 55 , 56 ]. They have also been used in mass screening programs for hepatitis B in both community outreach [ 24 , 57 ] and health-facility-based screening [ 52 , 53 , 58 , 59 , 60 , 61 , 62 ] in low-resource settings and shown great public health benefits. For example, in a community-based outreach screening program conducted in 75 camps in Southern India [ 63 ], the “screen and vaccinate/linkage to care” strategy led to over 7700 vaccinations in the camps and 162 people with high viral load getting treatment.…”
Section: Poc Tests For Hepatitis B and Their Clinical Performancementioning
confidence: 99%
“…The program was found to be highly cost-effective, with an ICER of US$540 per DALY averted compared to status quo where no publicly provided HBV screening or treatment was available. Integrating low-cost HBV POCs into existed healthcare services such as antenatal screening [ 52 , 58 , 107 ], blood donor screening [ 62 ] and HIV clinics [ 59 , 60 , 61 ] can be another solution to achieve scale-up of HBV testing [ 108 , 109 ]. Zhang et al [ 109 ] showed the integration of HBV screening within the existing antenatal care in Cambodia was highly cost-effective.…”
Section: Cost-effectiveness Of Using Pocs For Hepatitis Bmentioning
confidence: 99%
“…This prevalence was lower than the studies reported from Osogbo, Nigeria, Gambia, Yirgalem Hospital, Ethiopia, Deder Hospital, Eastern Ethiopia, Hawassa University referral hospital, Southwestern Nigeria, Yaounde-Cameroon, Eastern Region of Ghana, Buea Health District, Cameroon, Juba Teaching Hospital, Republic of South Sudan, Myanmar-Thailand Border and Shaanxi, China in which the prevalence of HBV infection among pregnant women were 16.5%, 9.20%, 7.2%, 6.9%, 7.8%, 8.3%, 7.7%, 10%, 9.7, 11%,6.2% and 7.07% respectively [12,13,15,17,[23][24][25][26][27][28][29][30].…”
Section: Prevalence Of Hepatitis B Virus In Pregnant Womenmentioning
confidence: 99%
“…The maternal and child health services are in rural areas, can be provided in Karen and Burmese language and is without costs. 5 34 35 …”
Section: Methods and Analysismentioning
confidence: 99%